Root cap border cells as regulators of rhizosphere microbiota - N. A. Omelyanchuk; V. A. Cherenko; E. V. Zemlyanskaya (Вавиловский журнал генетики и селекции)
A rhizosphere (a narrow area of soil around plant roots) is an ecological niche, within which beneficial microorganisms and pathogens compete with each other for organic carbon compounds and for the opportunity to colonize roots. The roots secrete rhizodeposits into the rhizosphere, which include border cells, products of root cell death and liquids secreted by living cells (root exudates). Border cells, which have their name due to their location in the soil next to the root (at the border of the root and soil), represent terminal differentiation of columella and adjacent lateral root cap cells. Border cells can detach from the root cap surface both as single cells and as cell layers. Border cells are constantly supplied to the soil throughout plant life, and the type and intensity of border cells’ sloughing depend on both plant species and soil conditions. Currently, data on the factors that control the type of border cells’ release and its regulation have been described in different plant species. Border cells are specialized for interaction with the environment, in particular, they are a living barrier between soil microbiota and roots. After separation of border cells from the root tip, transcription of primary metabolism genes decreases, whereas transcription of secondary metabolism genes as well as the synthesis and secretion of mucilage containing these metabolites along with extracellular DNA, proteoglycans and other substances increase. The mucilage that the border cells are embedded in serves both to attract microorganisms promoting plant growth and to protect plants from pathogens. In this review, we describe interactions of border cells with various types of microorganisms and demonstrate their importance for plant growth and disease resistance.